The impact of the use of training strategies Modern on improving the performance of employees in company’s Sudanese industrial public shareholding. Implementing is it on the Kenana Sugar Company - Hamed, Adam Ahmed Moussa; Ahmed, Shahabuddin Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to test the impact of the use of training strategies Modern on improving the performance of employees in company’s Sudanese industrial public shareholding. Implementing is it on the Kenana Sugar Company. Questionnaire was to collect data design has been distributed 73 questionnaires to different age and social groups. It has led the data analysis of a number of conclusions, which contribute the process of using modern methods in training on improving efficiency. The use of technology in the training process helps improve the performance of level training programs in line with the objectives of the company’s goals. This study concluded that a number of recommendations including the need for the industrial public shareholding companies to provide more attention and support to adopt clear strategies for training As well as the need to diversify, the training programs provided to its members. , And different approaches in training, and also need to focus on the use of modern technology as the basis for the implementation of its training programs in order to improve the performance of employees in these companies, and the need for advance planning of the training process to identify training needs to improve personnel performance where levels.